Imported Food Price Shocks and Socio-Political Instability : Do Fiscal Policy and Remittances Matter? - Meyimdjui, Carine (Washington, D.C. : International Monetary Fund, 2020)
Using a panel of 101 low- and middle-income countries with data covering the period 1980-2012, this paper applies various econometric approaches that deal with endogeneity issues to assess the impact of food price shocks on socio-political instability once fiscal policy and remittances have been accounted for. It focuses on import prices to reflect the vulnerability of importer countries / net-buyer households to food price shocks. The paper finds that import food price shocks strongly increase the likelihood of socio-political instability. This effect is greater in countries with lower levels of private credit and income per capita. On the other hand, while remittances seem to dampen the adverse effect of import food price shocks on socio-political instability in almost all countries, the mitigating role of fiscal policy is significant only in countries with low-levels of private credit.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet